Administrative Crime and Policing Trends in Ukraine 2019–2024 Under Wartime Disruption Offenses - Yuliia Shvets; Maksym Korniienko; Volodymyr Ivantsov; Sergii Galagan; Oleksii Botnarenko; Serhii Ternytskyi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study examines the behavior of policing-relevant administrative indicators in Ukraine across 2019–2024, spanning pre-escalation conditions and the period following the large-scale escalation of armed conflict beginning in February 2022. Using a measurement-aware, mixed-method descriptive design, we compile indicators across five domains: crime-processing backbone (registered and solved crimes), domestic-violence reporting, missing-persons caseload, institutional workload/service demand, and public trust in police. The evidence shows a clear discontinuity around 2022, where several domains stop behaving like extensions of pre-war patterns and begin reflecting a different measurement environment. Registered and solved crimes reverse direction after 2021 and expand through 2024, while the clearance proxy rises overall but does not move smoothly. Domestic-violence reports show volatility followed by post-2021 elevation, missing-persons magnitudes expand in post-2022 snapshots, and trust softens from 2023 to 2024. Cross-domain comparison reveals both convergence (multiple indicators shifting together around 2022) and divergence (clearance and trust moving differently from crime volumes). We interpret these patterns through an institutional-output lens: observed series are jointly shaped by changing reporting conditions, recording practices, coverage, and case processing constraints, not just by underlying prevalence. The study demonstrates a crisis-ready approach where indicators are reported faithfully to their public form, discontinuities are made explicit, and conclusions avoid over-claiming. Recommendations include pairing numbers with coverage/definitional metadata, treating cross-domain divergence as an audit trigger, and strengthening multi-source triangulation to distinguish changes in harm from changes in measurement.